A study on consumer awareness towards TM Merdeka Millionaire Reward Programme / Litah Kuyun - Kuyun, Litah (2007)
The research entitled "A STUDY ON CONSUMER AWARENESS TOWARDS TM MERDEKA MILLIONAIRE REWARD PROGRAMME" serves three main purposes; (i) to study the consumer awareness level of the TM Merdeka Millionaire Reward Programme; (ii) to identify factors that influence TM's customer to participate in TM Merdeka Millionaire Reward Programme; and (iii) to identify additional ways that can be used by TM in order to attract more participants in the program. The findings and analysis are the main content of the research to analyse the problems. It will help how to increase the awareness. From the survey result most of the consumers are aware of the TM Merdeka Millionaire Reward Programme, where the result showed 114 from 150 respondents are aware with the programme. In terms of respondents participation, there are still low, only 50 out of 100 respondents have participate with the programme. It means that there are still a large number of TM's customer that did not participate in this programme provided by Telekom Malaysia Berhad. Therefore TM should continue this programme for the next season, where the result showed that 94% of the respondents agreed to the suggestion that TM to continue this programme. It is hoped that by doing this research will support TM to increase the participation in TM Merdeka Millionaire Reward Programme for the next season. Most of the respondents are interested to know more about the programme provided by TM and are interested to participate with the programme.